2007
DOI: 10.1080/17453670710013915
|View full text |Cite
|
Sign up to set email alerts
|

Hamstring tendon autograft better than bone patellartendon bone autograft in ACL reconstruction A cumulative meta-analysis and clinically relevant sensitivity analysis applied to a previously published analysis

Abstract: Background Current debate on treatment options for anterior cruciate ligament (ACL) reconstruction complicate the choice between hamstring and bone patellartendon bone autografts. We hypothesized a priori that cumulative meta-analysis (a form of sensitivity analysis) might show that the evidence for reduction of morbidity by hamstring grafts could have been reached at an earlier time. Furthermore, we hypothesized a priori that modern state-of-the-art hamstring graft fixation technique would give similar result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
41
0
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(43 citation statements)
references
References 24 publications
1
41
0
1
Order By: Relevance
“…Thus laxity tests performed at 02 year follow-up was statistically significant suggesting improvement in the stability of knee between pre-operative and post-operative status of patients in our study. These results are comparable to the results achieved by various other authors Beynnon et al [17] Saccomanno et al [33] and Poolman et al [34] Functional Outcome H. E. Bourke et al [35] reported the outcome of 'isolated' anterior cruciate ligament (ACL) ruptures treated with anatomical endoscopic reconstruction using hamstring tendon autograft at a mean of 15 years. A total of 152 patients underwent subjective assessment at 15 years.…”
Section: Laxity Testssupporting
confidence: 78%
“…Thus laxity tests performed at 02 year follow-up was statistically significant suggesting improvement in the stability of knee between pre-operative and post-operative status of patients in our study. These results are comparable to the results achieved by various other authors Beynnon et al [17] Saccomanno et al [33] and Poolman et al [34] Functional Outcome H. E. Bourke et al [35] reported the outcome of 'isolated' anterior cruciate ligament (ACL) ruptures treated with anatomical endoscopic reconstruction using hamstring tendon autograft at a mean of 15 years. A total of 152 patients underwent subjective assessment at 15 years.…”
Section: Laxity Testssupporting
confidence: 78%
“…[7] Poolman et al [8] reported that newer hamstring graft fixation methods yielded similar stability as bone-patellar tendon-bone grafts. None of our patients had any clinical problem requiring revision surgery due to failure of fixation.…”
Section: Discussionmentioning
confidence: 99%
“…These results are comparable to the results achieved by various other authors world-wide. 4,9,20,21 In this study, we had one case of graft re-rupture, but it was not related to the surgical technique. One patient was diagnosed to have cyclops lesion on MRI resulting in painful restriction of terminal extension.…”
Section: Discussionmentioning
confidence: 99%